Geografski pogledi na družbo znanja v Sloveniji - Kozina, Jani (Georitem, 2012)
Studies on the knowledge society and regional innovation systems and their contribution to economic growth are already well established in research literature. This book ('Geographical Perspectives on the Knowledge Society in Slovenia') is based on a geographical analysis of connections between technological knowledge, competitiveness factors, and economic effects. It proceeds from the hypothesis that economic effectiveness in a region originates from the quality of human capital, in which innovations are the precondition for social progress, competitiveness, and developmental success. This article analyzes the spatial expansion of the knowledge society based on socioeconomic and development indicators in Slovenia. The key finding is that these areas are unevenly distributed. The high share of centers of national importance and neighboring suburban municipalities in emerging urban regions stands out in particular. Areas with a high percentage of creative professions are more innovative and their economic and social development is more successful.